The systematization of the mainstreaming of research training content Technician in Nursing - Lola Rosario Altamirano-Baquerizo Altamirano-Baquerizo; Roger Martínez-Isaac; Marlene Daley-Gonzalez (Santiago, 2016)
The work presented is from recognizing the training needs of the students of the Higher Technical career in Nursing Bolivarian Technological Institute of Technology, since it appears as regularly as research training is mainly associated with the search bibliographic information and not as a tool for solving professional problems, coupled with the project of certification. Why this paper aims to draft pedagogical nature reflections provide insight into the methodological guidelines for mainstreaming research training of Technician in Nursing in the Ecuadorian context. This result of the doctoral research carried out on this subject, with the application of empirical and theoretical methods which set the proposals that contribute to the solution of this problem.